Estimation of daily selenium intake by 3- to 5-year-old Japanese children based on selenium excretion in 24-h urine samples. (2019) - Nakamura, Yoshitaka; Fukushima, Michiko; Hoshi, Seiko; Chatt, Amares; Sakata, Takashi
Abstract: To evaluate the daily Se intake of 3- to 5-year-old Japanese children, we used seventy-two urine samples collected from fifty-three children (twenty-seven male and twenty-six female) from two cities in Miyagi prefecture, Japan. For measuring low Se concentrations with high precision, accuracy and rapidity in the 24-h urine samples, we developed an instrumental neutron activation analysis (INAA) method, that is without any chemical separation, using the short-lived 77m Se ( t 1/2 = 17·4 s) nuclide. The estimated Se intake of the fifty-three children was 51·5 (sd 30·2) µg/d (geometric mean: 42·7 µg/d). Ten subjects (three male and seven female), successfully provided 24-h urine samples over two or three consecutive days; their Se intake was 37·4 (sd 5·9) µg/d. Based on the logarithmically transformed data of these ten subjects, the ratio of intra-/inter-individual variances of usual Se intake was 16·7 (28·0/1·7) and geometric mean was 27·7 µg/d. The 5th to 95th percentile of usual Se intake of these ten subjects was 17·5 to 40·4 µg/d, which ranged between the recommended dietary allowance and tolerable upper intake level of Se by the Dietary Reference Intakes for Japanese (2015).